Subject object cognition / translated by Sergei Syrovatkin - "Lektorsky, V A" (Moscow, 1984)
In the book, a number of unresolved vital philosophical and methodological problems are dealt with. The author also critically considers the approaches to the cognitive relation characteristic of pre-Marxian and non-Marxist philosophy. The book is intended for readers interested in problems of epistemology, the methodology of science, the science, and the psychology of knowledge.
Keywords: Psychology